IT adoption and spatial agglomeration - a model of cumulative adoption in a small open economy - Bellone Flora (European Regional Science Association (ERSA), 2005)
I develop a model of cumulative ICT investments in a small open economy framework with differenciated inputs and imperfect competition borrowed to Ciccone and Matsuyama (1996). Within this framework, fixed adoption costs and pecuniary externalities based on strategic complementarities between users and producers of ICT-related inputs are what allow for agglomeration economies in ICT investments despite the abscence of transport costs. Moreover, expectations and the way alternative industrial structures allow them to be coordinated (monopolistic competition versus horizontally integrated monopoly) are key determinants of the likelyhood of an economic catching-up based on the intensive adoption of ICT inputs. Actually, three alternative growth paths with very different long-run outcome are allowed to emerge : 1) a "no-growth path” path in which the economy is trapped into primitive production processes; 2) a "transitory high growth path” in which the region underwents a process of adjustment to technological change and modernize its production processes by intensively adopting imported ICT-related inputs; 3) a "miracle growth path” where the regional economy find the adequate incentives not only to intensively adopt imported ICT inputs but also to develop and produce new ICT inputs.
Keywords: 330